2023
DOI: 10.1039/d3cy00054k
|View full text |Cite
|
Sign up to set email alerts
|

CoP decorated 2D/2D red phosphorus/B doped g-C3N4 type II heterojunction for boosted pure water splitting activity via the two-electron pathway

Abstract: CoP decorated 2D/2D red phosphorus/B doped g-C3N4 heterojunction enabled photocatalytic pure water splitting to produce H2 with a two-electron process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 88 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…[95] CoP decorated 2D/2D red phosphorus/B doped g-C 3 N 4 (CoP/RP/BCN) was prepared to construct type II heterojunction to achieve pure water splitting activity via the two-electron pathway. [25] As shown in Figure 5c, the photogenerated electrons in the CB of BCN were transferred to the surface of CoP by the electron route of RP, which reduced water into H 2 . Meanwhile, the photogenerated holes were aggregated in the VB of BCN to oxidize water and generate H 2 O 2 .…”
Section: Heterostructurementioning
confidence: 99%
See 1 more Smart Citation
“…[95] CoP decorated 2D/2D red phosphorus/B doped g-C 3 N 4 (CoP/RP/BCN) was prepared to construct type II heterojunction to achieve pure water splitting activity via the two-electron pathway. [25] As shown in Figure 5c, the photogenerated electrons in the CB of BCN were transferred to the surface of CoP by the electron route of RP, which reduced water into H 2 . Meanwhile, the photogenerated holes were aggregated in the VB of BCN to oxidize water and generate H 2 O 2 .…”
Section: Heterostructurementioning
confidence: 99%
“…On the other hand, typically four-electron pathway of water splitting (2H 2 O!2H 2 + O 2 ) requires an energy of 4×1.23 eV, resulting in thermodynamically more favorable than two-electron pathway. [25] However, the selectivity of water splitting pathway also depends on the O-binding free energy (ΔGO) of photocatalysts and the formation energy of H 2 O 2 (ΔGH 2 O 2 ). Under the condition of ΔGO > ΔGH 2 O 2 , the quick H 2 O 2 evolution kinetics reveal the potential of two-electron pathway with catalystinducement.…”
Section: Introductionmentioning
confidence: 99%
“…To compensate for the inadequate proffer of charge separation at the heterojunction interface and improve the sluggish surface reaction dynamics, the co-catalyst modification has been validated to effectively improve the photocatalytic activity by facilitating charge transport and decreasing the surface activation energy. 19–22 Compared with the loading of a single co-catalyst, dual co-catalyst loading with different functions provides rich active centers and migration channels for both electrons and holes, thus achieving increased charge separation and outstanding photocatalytic performance. 23–26 He et al reported the CdS nanorods decorated with both reduction co-catalyst Ag 2 S and oxidation co-catalyst NiS for drastically elevated hydrogen production performance.…”
Section: Introductionmentioning
confidence: 99%
“…g-C 3 N 4 is a valuable photocatalyst with the advantages of low cost, simple preparation and high chemical and thermal stabilities and has been widely explored to prepare heterogeneous catalysts for photocatalytic hydrogen production. 15 However, it exhibits a relatively narrow response range to visible light, fast charge recombination, and low specific surface area, which hinders its further application in efficient photocatalytic hydrogen production under visible light. 16 Overcoming the drawbacks shown by the MOF and g-C 3 N 4 , heterojunction composites fabricated using these materials have shown significant advantages for achieving photocatalytic hydrogen production.…”
Section: Introductionmentioning
confidence: 99%